2013
DOI: 10.1097/ccm.0b013e31828a3bbd
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intrahospital Transport in Ventilated Critically Ill Patients

Abstract: Intrahospital transport increases the risk of complications in ventilated critically ill patients. Continuous quality improvement programs should include specific procedures to minimize intrahospital transport-related risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 35 publications
4
129
2
12
Order By: Relevance
“…5,7,11,19,21,23,[26][27][28][29]39 Lahner et al 25 reports that anesthesiologists perform all transports; nurses do not routinely accompany patients during transport. Winter 40 recommends that an intrafacility transport be delayed until an adequately trained physician is present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,7,11,19,21,23,[26][27][28][29]39 Lahner et al 25 reports that anesthesiologists perform all transports; nurses do not routinely accompany patients during transport. Winter 40 recommends that an intrafacility transport be delayed until an adequately trained physician is present.…”
Section: Discussionmentioning
confidence: 99%
“…5,[24][25][26][27][28] This wide variation is largely based on differences in definitions of adverse events. As an example, in the study by Kue et al, 24 who reported an overall adverse event rate of 1.7%, technical events such as losing an intravenous catheter or equipment malfunction were excluded as adverse events.…”
Section: Adverse Events During Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-hospital transfers of NIV patients are usually made: 1) from the Emergency Department (ED) to the ICU or to another high-intensity ward with experience in handling NIV (e.g., the Respiratory Intermediate Care Unit), 2) between the ED or the ICU and the Radiology Department ( Figure 1); 3) between different areas of the latter unit; and 4) between the ED/ICU and specialized care units, such as the endoscopic or hemodynamic unit (16,17).…”
Section: Intra-hospital Transport and Nivmentioning
confidence: 99%
“…To date, a variety of different types of interfaces have been validated for NIV, but facial (full-face or oro-nasal) masks and helmets are the most widely used in the acute setting (16)(17)(18)(19). While ventilator modalities are set to a specific clinical goal, the choice of interface affects the prevention of leaks and patient comfort, both of which are closely related to the success of the technique (20)(21)(22)(23)(24).…”
Section: Interfaces and Circuitsmentioning
confidence: 99%